Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Berbantuan Media Mind Mapping Dilengkapi dengan LKPD Question Box untuk Meningkatkan Hasil Belajar Peserta Didik di SMP Negeri 2 Waingapu - Lewi, Chening Nonci; Bano, Vidriana Oktoviana; Ndjoeroemana, Yohana (Pustaka Digital Indonesia, 2025)
This study applies a cooperative learning model of the make a match type supported by mind mapping media and equipped with LKPD question box in order to improve student learning outcomes at SMP Negeri 2 Waingapu. This type of research is Classroom Action Research (CAR) which is carried out through three stages, namely pre-cycle, cycle I, and cycle II which include planning, implementation, observation, and reflection. This study uses a quantitative descriptive approach. The subjects of the study were 32 class VII C students in the even semester of the 2024/2025 academic year. The results show that the use of the make a match model assisted by mind mapping media and LKPD question box is effective in improving student learning outcomes in science subjects. The increase was seen in student learning outcomes from cycle I to cycle II, with the percentage of completion increasing from 40% to 91%. In the affective aspect, in cycle I there were 7 students in the good category, 9 were sufficient, and 16 were lacking. While in cycle II it increased to 11 very good, 18 good, and 3 sufficient. In conclusion, the use of this learning model has been proven to be able to encourage increased learning outcomes for students at SMP Negeri 2 Waingapu.